Interprofessional education for personalized medicine through technology-based learning. (June 2015) - Haga, Susanne B; Mills, Rachel; Aucoin, Julia; Taekman, Jeff
The delivery of personalized medicine utilizing genetic and genomic technologies is anticipated to involve many medical specialties. Interprofessional education will be key to the delivery of personalized medicine in order to reduce disjointed or uncoordinated clinical care, and optimize effective communication to promote patient understanding and engagement regarding the use of or need for these services. While several health professional organizations have endorsed and/or developed core competencies for genetics and genomics, the lack of interprofessional guidelines and training may hamper the delivery of coordinated personalized medicine. In this perspective, we consider the potential for interprofessional education and training using technology-based approaches, such as virtual simulation and gaming, compared with traditional educational approaches.